The Impact of Patent Disclosure Quality on Sustainable Innovation: A Qualitative Review of the Role of Patent Examiners - Benardi Benardi; Seger Santoso (LPPM STIE Kasih Bangsa, 2025)
This study aims to explore the influence of patent disclosure quality on sustainable innovation with a focus on the role of patent examiners. Through a qualitative literature review approach, this study analyzes previous studies that discuss the relationship between patent disclosure and sustainable innovation. The results show that high-quality patent disclosure can enhance collaboration between parties involved in the innovation process, as well as provide information needed for further technology development. The role of patent examiners is crucial in ensuring that the disclosure meets the required standards, thus supporting a more sustainable innovation process. Thus, this study underlines the importance of effective patent disclosure management and recommendations for policies that support sustainable innovation. These findings are expected to contribute to the understanding of the relationship between patent disclosure quality and sustainable innovation and encourage further research in this area